2019
DOI: 10.1103/physrevb.100.174410
|View full text |Cite
|
Sign up to set email alerts
|

Heisenberg pseudo-exchange and emergent anisotropies in field-driven pinwheel artificial spin ice

Abstract: Rotating all islands in square artificial spin ice (ASI) uniformly about their centres gives rise to the recently reported pinwheel ASI. At angles around 45 o , the antiferromagnetic ordering changes to ferromagnetic and the magnetic configurations of the system exhibit near-degeneracy, making it particularly sensitive to small perturbations. We investigate through micromagnetic modelling the influence of dipolar fields produced by physically extended islands in field-driven magnetisation processes in pinwheel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…While these topologies were found to be dependent on the angle of the applied reversal eld, we expect these to additionally be inuenced by the predicted intrinsic chirality of the system, in particular when the eld angle is close to zero. Moreover, the chiral boundaries of arrays with a similar geometry have been shown to play a role in the magnetization reversal process 31 and may compete with the intrinsic chirality studied here which occurs in the bulk of the array.…”
Section: Resultsmentioning
confidence: 89%
“…While these topologies were found to be dependent on the angle of the applied reversal eld, we expect these to additionally be inuenced by the predicted intrinsic chirality of the system, in particular when the eld angle is close to zero. Moreover, the chiral boundaries of arrays with a similar geometry have been shown to play a role in the magnetization reversal process 31 and may compete with the intrinsic chirality studied here which occurs in the bulk of the array.…”
Section: Resultsmentioning
confidence: 89%
“…Here, we use islands of length 470 nm, width 170 nm, and thickness 10 nm, arranged in a lattice with a nearest neighbor distance of 420 nm, in order to match our earlier work on this system. [ 31,37 ] A set of geometries is defined by island rotation angle, α, from pinwheel at α=0normalo to square at α=45normalo, as shown in Figure 1b. The models are, in part, defined by the island reversal barrier, which we quantify by the angular dependence of the island's coercive field.…”
Section: Interaction Modelsmentioning
confidence: 99%
“…In a previous work, we found that the experimentally observed reversal of pinwheel arrays [ 31 ] could not be replicated using a simple PD model, but that the main features could be reproduced through MM modeling. [ 37 ] It was recently reported that the use of the SW‐PD model also allows the magnetization reversal of pinwheel ASI to be reproduced. [ 41 ] While the SW‐PD model is a substantial improvement on the PD model, we will show that not all magnetization properties are reproduced in this model.…”
Section: Interaction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the structural analysis of the type discussed above, the ability to inspect the 4D dataset in this manner is particularly useful in magnetic imaging, where the source, either magnetic or crystalline, of apparent beam-shifts can be interrogated by navigating the 4D dataset using a color vector magnitude image produced from the analysis [examples of vector magnitude plots of this type may be seen in Paterson et al (2019)]. This type of beam-shift processing will be discussed further in Part III.…”
Section: Data Visualizationmentioning
confidence: 99%